2019
DOI: 10.1080/21691401.2018.1543192
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesized selenium nanoparticles using Spermacoce hispida as carrier of s-allyl glutathione: to accomplish hepatoprotective and nephroprotective activity against acetaminophen toxicity

Abstract: s-allyl glutathione (SAG) an analogue of glutathione is explored for its antioxidative and liver protection property in recent years. Selenium nanoparticles (Sh-SeNPs) were synthesized using medicinal plant Spermacoce hispida and conjugated with SAG (SAG-Sh-SeNPs). SAG-Sh-SeNPs and Sh-SeNPs were characterized using by Fourier transform infrared spectroscopy, Transmission electron microscopy, Energy dispersive X-ray analysis, X-ray diffraction analysis and zeta potential analysis. SAG-Sh-SeNPs and Sh-SeNPs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 50 publications
(72 reference statements)
0
13
0
Order By: Relevance
“… 3 , 45 , 46 Interestingly, green synthesized SeNPs using LYC provided more significant renoprotection than using sodium selenite or LYC alone. Krishnan et al 24 reported that SeNPs loaded with Spermacoce hispida exhibited many nephroprotective and hepatoprotective effects against acetaminophen toxicity compared to the sole treatment with SeNPs in rats. Similarly, Ramamurthy et al 26 stated that green synthesized SeNPs using fenugreek seed extract notably inhibited the cell growth in human breast cancer cells in dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 3 , 45 , 46 Interestingly, green synthesized SeNPs using LYC provided more significant renoprotection than using sodium selenite or LYC alone. Krishnan et al 24 reported that SeNPs loaded with Spermacoce hispida exhibited many nephroprotective and hepatoprotective effects against acetaminophen toxicity compared to the sole treatment with SeNPs in rats. Similarly, Ramamurthy et al 26 stated that green synthesized SeNPs using fenugreek seed extract notably inhibited the cell growth in human breast cancer cells in dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Instead of the chemical method, great attention has been drawn recently to the eco-friendly or green synthesis of SeNPS using biomolecules (plant proteins and polysaccharides) as a capping agent during processing. 24–26 The eco-friendly approach for SeNPs synthesis is better than other physical and chemical methods due to its low cost, minimum hazard, and high potency. 26 Recent studies stated that treatment with green synthesized SeNPs had noticeable antioxidant and anti-apoptotic activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, selenium, phosphorus, and carbon are essential elements for human physiology [ 183 , 184 ]. Currently, nanoparticles based on these elements have been adopted for AKI treatment, with excellent therapeutic effects and extremely low side effects [ [185] , [186] , [187] , [188] , [189] ]. For example, Rosenkranz et al adopted selenium-doped carbon quantum dots (SeCQDs) for AKI antioxidant therapy ( Fig.…”
Section: Nano-rons-sacrificial Agentsmentioning
confidence: 99%
“…Selenium nanoparticles have been shown to possess therapeutic potential against various cancer cells, microbial pathogens, and viruses and protect from hepatic diseases [218,[248][249][250], diabetes [251][252][253], and neurological diseases [254][255][256]. However, few studies have reported the therapeutic effects of selenium nanoparticles on bone-related conditions.…”
Section: Effect Of Selenium Nanoparticles On Bone Healthmentioning
confidence: 99%